PEMANFAATAN DANA REBOISASI KABUPATEN PELALAWAN TAHUN 2017 - Asikin, Nurul; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Reforestation Fund in accordance with Government Regulation Number 35 of 2002 concerning the Reforestation Fund aims to finance the implementation of Forest Rehabilitation activities. The existence of the Reforestation Fund in the regions actually raises problems, from the beginning until 2017 it is not able to be utilized optimally, this is evidenced by the budget that always settles in the regional treasury. Not optimal absorption of Reforestation Funds has led to negative SiLPA, one of which is due to the limitations of local governments to use it. This study rests on theoretical analysis of Effectiveness, Efficiency, and Inhibiting Factors for Policy Implementation. Done with a qualitative approach and descriptive analysis.This study shows that the Reforestation Fund intended to finance the implementation of Forest Rehabilitation activities was not able to be utilized properly by the Pelalawan District Government. On the other hand the condition of the forest continues to be alarming and requires an effort to restore (Forest Rehabilitation). The Reforestation Fund should be potential enough if it is able to be used properly to finance these activities. In Government Regulation Number 35 of 2002 concerning Reforestation Funds, it is stated that the Reforestation Fund area is used only to finance reforestation and rehabilitation activities and supporting activities. The series of implementation of Forest Reahabilitation is not only at the reforestation stage, including the cost of procuring equipment, accessing locations and so on. Reforestation funds are not allowed to be used other than reforestation activities for which the government needs to provide other budgets. Strict rules and no technical instructions for using them in detail are also often a source of problems for regions in using the budget. By reason of not wanting to take risks and lack of effort and regional commitment, the Reforestation Fund was allowed to settle into a large number of SiLPA.Keywords: Reforestation Funds, Utilization of Reforestation Funds, Forest Rehabilitation